Human papillomavirus mRNA and DNA testing in women with atypical squamous cells of undetermined significance: A prospective cohort study. Issue 8 (26th April 2016) - Thomsen, Louise T.; Dehlendorff, Christian; Junge, Jette; Waldstrøm, Marianne; Schledermann, Doris; Frederiksen, Kirsten; Kjaer, Susanne K.
Abstract : In this prospective cohort study, we compared the performance of human papillomavirus (HPV) mRNA and DNA testing of women with atypical squamous cells of undetermined significance (ASC‐US) during cervical cancer screening. Using a nationwide Danish pathology register, we identified women aged 30–65 years with ASC‐US during 2005–2011 who were tested for HPV16/18/31/33/45 mRNA using PreTect HPV‐Proofer ( n  = 3, 226) or for high‐risk HPV (hrHPV) DNA using Hybrid Capture 2 (HC2) ( n  = 9, 405) or Linear Array HPV‐Genotyping test (LA) ( n  = 1, 533). Women with ≥1 subsequent examination in the register ( n  = 13, 729) were followed for up to 9.5 years for high‐grade cervical intraepithelial neoplasia (CIN) or cancer. After 3 years' follow‐up, mRNA testing had higher specificity for CIN3 or worse (CIN3+) than HC2 testing (88.1% [95% confidence interval (CI): 86.8–89.6%] versus 59.3% [95% CI: 58.1–60.4%]) and higher positive predictive value (PPV) (38.2% [95% CI: 33.8%–43.1%] versus 19.5% [95% CI: 17.8–20.9%]). However, the sensitivity of mRNA testing was lower than that of HC2 testing (66.7% [95% CI: 59.3–74.5%] versus 97.0% [95% CI: 95.5–98.4%]), and women testing mRNA negative had higher 3‐year risk for CIN3+ than those testing HC2 negative (3.2% [95% CI: 2.2–4.2%] versus 0.5% [95% CI: 0.3–0.7%]). Patterns were similar after 18 months and 5 years'; follow‐up; for CIN2+ and cancer as outcomes; across all age groups; and when comparing mRNA testing to hrHPV DNA testing using LA. In conclusion, the HPV16/18/31/33/45 mRNA test is not optimal for ASC‐US triage due to its low sensitivity and the substantial risk for precancer following a negative test. Abstract : What's new? Testing for human papillomavirus (HPV) DNA in women with atypical squamous cells of undetermined significance (ASC‐US) is widely implemented in cervical cancer screening, despite suboptimal specificity. An emerging alternative is HPV mRNA testing, though few prospective studies have compared HPV mRNA and DNA testing for ASC‐US triage. Here, in a cohort of 13, 729 women, a commercial mRNA test for five different HPV types was found to be more specific but far less sensitive for high‐grade cervical intraepithelial neoplasia than widely used HPV DNA tests. The authors conclude that five‐type HPV mRNA testing is not optimal for ASC‐US triage.